Monitoring Efek Samping Obat Antituberkulosis terhadap Pasien Tuberkulosis Paru di Rumah Sakit X Malang - Sindi Wahyu Arianti; Agung Permata; Novyananda Salmasfattah; Magdalena Tania Tnesi (Indonesian Journal of Pharmaceutical Education, 2023)
Tuberculosis (TB) is an infectious disease caused by Mycobacterium tuberculosis which spreads through the air and can be a major cause of poor health and is even one of the main causes of death throughout the world. The recommended treatment for TB is the use of antibiotics, but some patients experience side effects, both severe and mild. Patients diagnosed with pulmonary TB at X Hospital Malang who experienced pharmacological side effects based on medical record data will be used in this study. There will be 55 pulmonary TB patients in 2022 at X Hospital in Malang. Patients who were more likely to contract TB in this study were men (54.5%) with a maximum age range of 60 years (29.1%), and the most frequent impact was shortness of breath (43.6%). Meanwhile, the number of patients who did not experience side effects was 7.2%. Other effects that often occur are reduced appetite, nausea and coughing. Therefore, side effects that occur when using OAT, both frequent and rare effects, still need to be watched out for by health workers. This needs to be done so that the side effects that occur can be minimized and patient compliance also increases because of the minimal side effects experienced.